Safflower heterosis for yield and its contributed characters: Safflower heterosis for yield and its contributed characters - SANGITA U FATAK,; S J GAHUKAR,; R D RATNAPARKHI, (Journal of Oilseeds Research, 2023)
Safflower (Carthamus tinctorius L.) is one of the major edible oilseed crops grown in winter season in India. The first safflower hybrid released in India for commercial cultivation in all safflower growing regions was based on genetic male sterility system. Twenty two hybrids were tested using line x tester design involving two cytoplasmic male sterile lines during rabi 2018, using Randomized block design with three replications. Twenty two along with three checks 'A-1, PBNS-12, PKV Pink' were evaluated at the field of Oilseeds Research Unit, Dr. PDKV, Akola during rabi 2019-2020 to estimate extent of heterosis in safflower genotypes. Among all the crosses, AKS CMS 2A x GMU 1183 (46.15 % and 44.30%) exhibited highly significant and positive average heterosis for number of seeds per plant over mid and better parent. crosses, AKS CMS 2A x GMU 184 (49.26% and 34.44%) exhibited highly significant and positive average heterosis for 100 seed weight, whereas, cross AKS CMS 2A x GMU 5149 (15.28% and 9.32%) exhibited highly significant and positive average heterosis for volume weight. The highest heterosis and heterobeltiosis in desirable direction were recorded for seed yield per plant in AKS CMS 2A x GMU 1654 (246.96. %) and the cross AKS CMS 3A x GMU 1183 (206.75%) showed highest and significantly positive standard heterosis over the checks i.e. PKV PINK, AKS 207 and PBNS-12.Biotechnological tools, such as genetic engineering need to be perfected for incorporation of mitochondrial male sterility causing factor of sunflower into safflower to develop safflower hybrids which can be more easily produced.